If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 4r = -15 + 6r Solving 1 + 4r = -15 + 6r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-6r' to each side of the equation. 1 + 4r + -6r = -15 + 6r + -6r Combine like terms: 4r + -6r = -2r 1 + -2r = -15 + 6r + -6r Combine like terms: 6r + -6r = 0 1 + -2r = -15 + 0 1 + -2r = -15 Add '-1' to each side of the equation. 1 + -1 + -2r = -15 + -1 Combine like terms: 1 + -1 = 0 0 + -2r = -15 + -1 -2r = -15 + -1 Combine like terms: -15 + -1 = -16 -2r = -16 Divide each side by '-2'. r = 8 Simplifying r = 8
| 3x+-1=12x-64 | | 3(1/3)3 | | 5e+7e-9-e=84-4e | | (1/3)(1/3)(1/3)3=a | | 4/5y-8+=2/5+16 | | 8/2x=15/60 | | 7(k-3)= | | 2a+3b+7c= | | 3x+54y-12=0 | | 6(3-4y)= | | n+29=48 | | -4(-2b-7)=-44 | | 1.84/2.85=5.14/t | | 3i*x=y | | 2(5t-4)+6=40-t | | 49.2=1.5h | | 2(4m+1)=3 | | 114/95=95/x | | 6.4=16y | | xx/7-3=4 | | (2x-7)3=10x-9 | | -43=x/16 | | x-1=6/x | | 6x^3+56=53x-x^2 | | 7=5/6b-8 | | Y^2+3y=x | | (6+4x)*(15x+25)=0 | | F(x)=4*logx | | 3485x^2-311107.5x-18855000=0 | | n/36=17/72 | | 7w+6-3w=6 | | 4(2b-5)=2b+10 |